GAMIFICATION AS BUSINESS PRINCIPLE AND APPLICATION IN FRANCHISE COFFEE SHOP BUSINESS (CASE STUDY : KOPI LAIN HATI FRANCHISE) - Sujono, Jansen
Gamification is the application of game features and elements, into non-game context for the purpose of promoting motivation and engagement. In the Thesis context, Gamification will be Introduced as a Business Foundation concept and applied to Franchise Business with Brand “Kopi Lain Hati”. “Kopi Lain Hati” is The New Millennials’ Coffee Shop that gain massive popularity in early 2019 in Indonesia. The business began as new branch of Franchise in Bandung in late of December 2019. As the business has only started and strive to grow in rapid state, Kopi Lain Hati face several business challenges. This thesis will explore both internal and external elements for the business, and applying Gamification as the solution in improving business mode and strategy. In addition to creating sustainable business factor, the business strive a mission to reach Capital Return of Investment as soon as possible. Data in Gamification as Business Solution extracted from published paper and reports of Gamification by academics and Business Consultancy Agency that applied Gamification. With the Introduction of Gamification as foundation and Business Philosophy, we can design Customer Journey Map and found out about intrinsic motivation of customer. From there we can have better and optimized development tool and instrument to make effective effort. Gamification Strategy expected to raise quality and numbers in Sales, Marketing, and Human Resource aspects. With the direct application of Gamification instrument in Business, we can obtain data to study, observe and use as a benchmark and template to be optimized in the further Business development. The Business then took off the analysis theory, and start creating Gamification instrument, at first, in the form of membership card. 4 The instrument of Gamification which include provoking game mechanics have proven to excel in its performance. Through the Gamification strategy, the business would like to adapt and plan even further strategy with the philosophy. In the Last Chapter, conclusive statement will be made, and will determined the effectivity of Gamification Business Plan in Coffee Shop business. Further Plan and Research also included in next business development.